Adopsi Cloud Computing UMKM DKI Jakarta: Peran Kesiapan Teknologi dan Pembelajaran Organisasi - Ruslaini Ruslaini; Muhammad Rizal (Universitas Veteran Bangun Nusantara, 2022)
This study investigates how organizational learning and technological readiness affect cloud computing adoption strategies among Jakarta's Micro, Small and Medium-Sized Enterprises (MSMEs). The research methodology employed is qualitative with a phenomenological approach. Data were collected through in-depth interviews with MSME owners, managers, and IT professionals, selected using purposive sampling to ensure the variation and relevance of respondents to the research topic. The data obtained were analyzed using thematic analysis to identify and understand the patterns of interaction between technology readiness, organizational learning, and cloud computing adoption. The findings indicate that technology readiness, which includes adequate infrastructure and trained human resources, is a key determinant of cloud computing adoption among MSMEs in Jakarta. Additionally, organizational learning was found to assist MSMEs in overcoming challenges associated with adopting new technologies.